2007
DOI: 10.1093/dnares/dsm008
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Expressed Sequence Tags from the Fungus Aspergillus oryzae Cultured Under Different Conditions

Abstract: We performed random sequencing of cDNAs from nine biologically or industrially important cultures of the industrially valuable fungus Aspergillus oryzae to obtain expressed sequence tags (ESTs). Consequently, 21 446 raw ESTs were accumulated and subsequently assembled to 7589 non-redundant consensus sequences (contigs). Among all contigs, 5491 (72.4%) were derived from only a particular culture. These included 4735 (62.4%) singletons, i.e. lone ESTs overlapping with no others. These data showed that considerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 45 publications
1
56
0
Order By: Relevance
“…Gene AO090020000351 is one of the predicted genes encoding an extracellular serine-type carboxypeptidase. According to the results of an EST analysis of A. oryzae RIB40 (http://riodb.ibase.aist.go.jp/ffdb/ index.html), 26) a transcript of AO090020000351 was found in hyphae cultured not only in liquid media but also in solid media such as soy bean and rice. On the other hand, transcripts of other predicted genes encoding extracellular serine-type carboxypeptidase were found in hyphae cultured only in liquid or solid medium.…”
Section: Discussionmentioning
confidence: 99%
“…Gene AO090020000351 is one of the predicted genes encoding an extracellular serine-type carboxypeptidase. According to the results of an EST analysis of A. oryzae RIB40 (http://riodb.ibase.aist.go.jp/ffdb/ index.html), 26) a transcript of AO090020000351 was found in hyphae cultured not only in liquid media but also in solid media such as soy bean and rice. On the other hand, transcripts of other predicted genes encoding extracellular serine-type carboxypeptidase were found in hyphae cultured only in liquid or solid medium.…”
Section: Discussionmentioning
confidence: 99%
“…A BlastP search of the sequenced A. oryzae genome (Machida, et al, 2005) for proteins similar to Ayg1p revealed a potential functional complement in this heterologous host, the transcription of which was supported under standard laboratory conditions by detection of an expressed sequence tag (AoEST6890) from a conidial cDNA library (Akao, et al, 2007). Furthermore, the purified Pks1 SAT monodomain was found to selectively transfer acetyl in disparity with labeledprecursor incorporation experiments .…”
Section: Introductionmentioning
confidence: 96%
“…This result was expected because MFS transporters are a ubiquitous group of proteins involved in the transport of a wide range of compounds, including external elements and toxins (Saier et al, 1999;Vardy et al, 2004). In the Aspergillus oryzae genome, 63.9 % of transporters are MFS type, involved in secondary metabolism (Akao et al, 2007). The analysis of a gene encoding MFS transporter-like protein (CTB4) in Cercospora nicotianae provided genetic evidence to support its role in virulence by cercosporin accumulation (Choquer et al, 2007).…”
Section: Transporter Proteins In T Rubrum Pathogenesismentioning
confidence: 99%